A prospective study comparing itraconazole alone versus systemic steroids alone as adjuncts to topical steroids in the post‐operative management of allergic fungal rhinosinusitis. (13th December 2022) - Salil, Amala; Joy, Nedha; Faizal, Bini
Abstract: Objectives: The objective of this study was to compare the efficacy of itraconazole and systemic steroids as an adjuvant to topical steroids in post‐operative patients with allergic fungal rhinosinusitis (AFRS) using both subjective and objective outcome measurements. Design: A prospective comparative study. Setting: A tertiary care centre. Participants: Sixty patients diagnosed with AFRS were included. Patients with chronic systemic illness and those undergoing revision surgery were excluded. Post‐operative patients were divided into two groups of 30 each which received itraconazole 400 mg OD or methylprednisolone in tapering doses over 6 weeks. Main outcome measures: The outcomes were measured at the end of 6 weeks—Kupferberg endoscopic staging, absolute eosinophilic count (AEC), serum immunoglobulin (IgE), and Sino Nasal Outcome Test‐20 scores. Results: Our study showed no statistical significance in outcomes between the two groups treated with itraconazole and methylprednisolone regarding recurrence, AEC, IgE and quality of life assessment ( p < 0.01). Conclusion: Itraconazole was comparable to methylprednisolone in preventing disease recurrence in the post‐operative management of AFRS. It may be a viable alternative to replacing systemic steroids where the latter may be contraindicated. Itraconazole given at a dose of 400 mg once daily for 6 weeks was a safe dose.